Primary Oral Malignant Melanoma - Panjab V Wanjari; Ashish M Warhekar; Sangeeta P Wanjari; Vanaja Reddy; Satyajitraje Tekade; Pallavi Shrivastava (Wolters Kluwer Medknow Publications, 2011)
Malignant melanoma (MM) is a malignant neoplasm of epidermal melanocytes. Primary malignant melanoma (PMM) is rarely found in the oral cavity. It is estimated at between 0.2 and 8% of all melanomas and approximately four times more frequently in the oral mucosa of the upper jaw, usually on the palate and anterior gingiva. It is more prevalent in the older population having 50 to 80 years of age. Males are more commonly affected than females. Some rare cases of involvement of lip, mandibular gingiva and buccal mucosa were also reported previously. Here, we are reporting a rare case of MM in the oral cavity of 60-year-old male patient involving mandibular gingiva.